JANUBIY SUG‘D HUDUDIDAGI YO‘L BO‘YI INSHOOTLAR. QARSHI – KERKI YO‘NALISHIDAGI TALIMARJON SARDOBASI HAQIDA BA’ZI MULOHAZALAR - Elmuratov Ortiq (Social science and innovation, 2023)
This article provides information about the etymology of Talimardzhan, the roadside structures located on the Karshi-Kerki route – sardoba, caravanserai and rabats, the study of Talimardzhan’s sardoba by young researchers